PENGARUH KUALITAS PELAYANAN, HARGA DAN KUALITAS PRODUK TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Konsumen Resto Ayam Nelongso Sawojajar) - Ahmad Farid Wahyudi; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study is aimed to know the effect of the service quality, the price and the product quality on customers’ loyalty through satisfaction as intervening variable (a case study of Ayam Nelongso Sawojajar restaurant customers). This study used qualitative research approach and this study is an explanatory research. The population of this study is all the consumers who become the customers of Ayam Nelongso Sawojajar restaurant.  The purposive sampling technique was used in this study to determine the sample.   The data was gained from distributing the questionnaire to 99 respondents. The instrument used for collect the data was questionnaire and for the data analysis, the method used was path analysis.  Based on the data analysis and the hypothesis testing, the result of this study is: The service quality and the product quality on customers’ loyalty of the variables’ satisfaction is positively and significantly affected and for the price on satisfaction as the intervening variable is not significantly affected. Based on the statement above, it can be concluded that the service quality, the price and the product quality on customers’ loyalty through variables’ satisfaction is positively and significantly affected.  Keywords : service quality, price, product quality, satisfaction, customers loyalty